A cell-laden hybrid fiber/hydrogel composite for ligament regeneration with improved cell delivery and infiltration. (25th September 2017) - Kim, Jeong Hwa; Choi, Yeong-Jin; Yi, Hee-Gyeong; Wang, Joon Ho; Cho, Dong-Woo; Jeong, Young Hun
Abstract: Ligament, a fibrous connective tissue between bones, is a unique tissue in human anatomy because it has complex viscoelastic properties and is very tough. Moreover, it is an important tissue for regeneration because frequent injuries occur, but there are limited types of substitutes that can be used as a tissue replacement. In this study, we present a stem cell-laden fiber/hydrogel composite structure with a layered fibrous structure, which can enhance cell infiltration, topographical cue and mechanical properties. It can promote cell viability, proliferation, and differentiation of the ligament phenotype with the help of a growth factor. The mechanical properties of the developed structure were experimentally identified using tensile tests, while cell viability and various functionalities were verified through culture tests using mesenchymal stem cells.